Robust Food Waste Management Method for Food Services (Romance) : Final report - Kettunen, Marita; Silvennoinen, Kirsi; Kostensalo, Joel; Lampi, Vesa (Luonnonvarakeskus, 2025)
Robust Food Waste Management Method for Food Services (ROMANCE) project aimed to identify effective solutions for reducing food waste, motivating staff, and fostering a waste prevention culture within food services. This report presents the results of food waste monitoring conducted in pilot restaurants alongside findings from the project's experiments, feedback book initiative, food waste mentor program, and motivational feature of the Lukeloki application. The food waste monitoring focused on public food services and was successfully carried out in 39 units across 10 organizations, including 23 schools, 9 daycare centres, and 7 elderly care facilities. On average, 22.3% of the prepared food became wasted, of which 15.3% being serving waste, 6.7% plate leftovers, and 0.3% kitchen waste. Food waste per customer was highest in elderly care facilities (285g), followed by daycare centres (166g) and schools (52g). The higher food waste rates in elderly care facilities and daycare centres were attributed to factors such as cart service and the larger number of meals served. The most significant sources of serving waste included meat main dishes (16%), porridges (16%), carbohydrate side dishes (15%), and fish main dishes (10%). The feedback book experiment aimed to modernize the traditional feedback books found in restaurant lobbies by providing a digital tool for collecting customer feedback and enhancing interaction. Integrated into the Lukeloki platform, the feedback book allowed customers to share feedback via QR codes using their smart phones. Although it aimed to help restaurants improve their operations, including waste management, the response rate was low. Future development should focus on enhancing interaction, diversifying questions and simplifying implementation in different environments. The food waste mentoring programme was a peer-learning and support initiative for food service professionals, where participants acted as waste mentors in their workplaces. The programme was tested with three small peer groups: meal service employees, public food service managers, and company specialists. Feedback indicated the programme was suitable for professionals in various roles and organizations, promoting waste management improvements through the exchange of best practices and peer support. The motivational feature in the Lukeloki application aimed to encourage kitchen staff to record food waste regularly. Tested in 42 locations which participated in waste monitoring, the motivational messages included daily greetings and site-specific waste data on the application. While designed to be non-intrusive, feedback revealed that the messages often went unnoticed, presenting a challenge for future refinement.
Keywords: food waste; food waste management; food services; restaurants; experiments; peer learning; customer feedback